CLINICAL SIGNS AND DIAGNOSIS OF POSTOPERATIVE ABDOMINAL ABSCESSES - Bobobekov, A.R. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. In recent years, thanks to the introduction of modern technologies into clinical practice, the quality of diagnosis of postoperative abdominal abscesses has significantly improved. Material and methods. This study is based on the experience of treating 63 patients with postoperative abdominal abscesses. Results. With postoperative abscesses of the abdominal cavity, there are violations of the function of external respiration and biochemical parameters of the blood, the degree and depth of which are more pronounced in the localization of the purulent process over the liver. Conclusion. For the diagnosis of postoperative abscesses of the abdominal cavity, along with clinical and laboratory research methods, radiography of the chest and abdominal cavities, ultrasound and computed tomography are of particular importance.